Octave-Spanning Supercontinuum Generation From an NALM Mode-Locked Yb-Fiber Laser System - Zhengru Guo; Qiang Hao; Song Yang; Tingting Liu; Hong Hu; Heping Zeng (IEEE Photonics Journal, 2017)
We demonstrate a broadband all polarization-maintaining Yb-fiber laser system that provides 137-nJ pulse at 140-fs duration. The pulses are generated in a passively mode-locked laser in which the nonlinear amplifying loop mirror acts as the mode locker, an integrated nonreciprocal device biases π/2 phase shift to reduce the mode locking threshold, and a pair of gratings are involved to force the oscillator operating in its quietest mode. Self-started mode locking is first achieved in multiple-pulse regime with 250-mW pump power, and stable single-pulse operation with 1.1-ps pulse duration, 75-pJ energy, and 29-nm spectral width are obtained subsequently when the pump power is decreased to 135 mW. Being amplified and spectral broadened, the laser pulses lead to an fceo signal with >30-dB signal-to-noise ratio (SNR) which is suitable for frequency comb stabilization.